2016
DOI: 10.1242/dev.138172
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of induced pluripotency: from basic mechanisms to therapeutic applications

Abstract: Ten years ago, the discovery that mature somatic cells could be reprogrammed into induced pluripotent stem cells (iPSCs) redefined the stem cell field and brought about a wealth of opportunities for both basic research and clinical applications. To celebrate the tenth anniversary of the discovery, the International Society for Stem Cell Research (ISSCR) and Center for iPS Cell Research and Application (CiRA), Kyoto University, together held the symposium 'Pluripotency: From Basic Science to Therapeutic Applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The first iPSC lines were generated by genome integrating retroviruses, which involves risks of insertional mutagenesis, unwanted residual expression of exogenous genes, which can hamper differentiation, or spontaneous reactivation of foreign genes during differentiation [125] . Today iPSCs are reprogrammed with integration-free methods, for instance using RNA based methods [126] . iPSCs have certain advantages over hESC; they allow generation of patient- and disease-specific hiPSCs, and they do not face the same ethical, political, and religious issues related to human embryo use.…”
Section: Novel Disease-relevant Human Cell Modelsmentioning
confidence: 99%
“…The first iPSC lines were generated by genome integrating retroviruses, which involves risks of insertional mutagenesis, unwanted residual expression of exogenous genes, which can hamper differentiation, or spontaneous reactivation of foreign genes during differentiation [125] . Today iPSCs are reprogrammed with integration-free methods, for instance using RNA based methods [126] . iPSCs have certain advantages over hESC; they allow generation of patient- and disease-specific hiPSCs, and they do not face the same ethical, political, and religious issues related to human embryo use.…”
Section: Novel Disease-relevant Human Cell Modelsmentioning
confidence: 99%
“…However, it appears that the former strategy is very time consuming and quite costly as extensive quality control (such as entire genome sequencing) needs to be performed on each of the individual patient-specific iPSC lines owing to the elevated risk of generating random mutations, which could possibly lead to tumor formation during the iPSC generation protocol (Kamao et al, 2014). Homozygous HLA matched iPSC quality tested, banked and clinically safe cell lines from healthy donors (like those found at the CiRA Center, Kyoto University, Japan) also hold much promise for stem cell based therapies (Sugita et al, 2016; Takahashi and Yamanaka, 2016), but the current limited number of lines available makes this an option for only a small percent of the world's population (Karagiannis and Eto, 2016; Sakurai et al, 2016). In a recent interview, Shinya Yamanaka, who developed the strategy for iPSC generation (Takahashi and Yamanaka, 2006, 2016) suggested that iPSCs would likely only be useful for treating approximately nine human diseases (spinal cord injury, joint disorders, Parkinson's, specific blood disorders, heart and liver failure, retinal and corneal diseases, and diabetes) over the next decade or so, and IVD-related diseases were not among them (Ravven, 2017).…”
Section: Will Ipscs Play a Significant Role In Ivd Regenerationmentioning
confidence: 99%
“…Somatic cell reprogramming can be used to generate induced pluripotent stem (iPS) cells. Reprogramming is commonly achieved by overexpressing four transcription factors, Oct4, Sox2, Klf4 and c-Myc (referred to as the OSKM cocktail) (Takahashi and Yamanaka, 2006;Karagiannis and Eto, 2016). Other gene combinations have been used, such as the OSNL cocktail embryos, cESCs are able to participate in the formation of all the somatic tissues and product chimeric embryos.…”
Section: Re-capturing Avian Pluripotency In Vitromentioning
confidence: 99%